Impact of Working Conditions, Flexibility, and Compensation on the Performance of Indonesian Migrant Workers in Australia: Mediating Role of Job Satisfaction - Albert Lianto; Ramadania; Marumpe, Dody Pratama; Daud, Ilzar; Hasanudin (Yayasan Sinergi Kawula Muda, 2025)
International migration, particularly involving Indonesian migrant workers (TKI) in Australia, has become significant, with nearly 100,000 TKI recorded in 2022. This study investigates the factors influencing their migration decision, focusing on working conditions, work flexibility, and compensation. A total of 149 respondents of Indonesian migrant workers in Australia completed the questionnaires, collected using non-probability and snowball sampling techniques. It was analysed using Structural Equation Modeling (SEM) with SmartPLS 3 software. The outcome reveals that working conditions positively affect performance, confirming that a supportive work environment enhances productivity. In contrast, work flexibility negatively impacts performance, while compensation shows a positive but statistically insignificant effect. Job satisfaction emerges as a critical mediator, with satisfied employees performing better. The findings suggest companies should improve working conditions and compensation systems to enhance job satisfaction and performance. Additionally, the study provides insights for the Indonesian Government on the importance of labour policies that promote worker welfare, such as fair wages and improved conditions, potentially reducing reliance on international migration. Future studies should incorporate a wider array of variables and a more diverse group of respondents to enhance generalizability.